A review of Tenofovir Disoproxil Fumarate associated nephrotoxicity among People Living with HIV: Burden, risk factors and solutions - Edwin Sam Asirvatham; Varsha Ranjan; Chhavi Garg; Charishma Jones Sarman; Mahalingam Periasamy; Vijay Yeldandi; Sunita Upadhyaya; Bhawna Rao (Elsevier, 2024)
Background: Tenofovir Disoproxil Fumarate (TDF) is one of the first-line antiretroviral therapy (ART) recommended for all treatment naïve People Living with HIV (PLHIV). However, evidence indicates increasing TDF-associated nephrotoxicity among PLHIV due to longer duration of treatment and longevity that raises clinical and programmatic concerns. This review aims to understand the extent of TDF-induced nephrotoxicity and associated factors. Methods: The article is based on a comprehensive scoping review of journal articles, reports and guidelines related to the use of TDF-based ART regimens in electronic databases such as the National Library of Medicine (PubMed), Google Scholar, Web of Science, Scopus and other relevant search engines. Results: The review provides evidence on the burden of nephrotoxicity due to TDF among PLHIV and its variations across geographic regions and population groups. The review highlights the key factors associated with TDF-induced nephrotoxicity which include age, gender, nutrition status (BMI), duration of treatment with TDF, baseline creatinine, baseline CD4 count, WHO HIV stage of disease and presence of comorbid conditions. The review also emphasizes the importance of baseline and regular renal monitoring and early detection of TDF-induced nephrotoxicity to avoid irreversible tubulointerstitial damage through simple laboratory investigations such as glomerular filtration rate (GFR), blood urea nitrogen, serum creatinine and creatinine clearance. Conclusion: The burden of TDF-associated nephrotoxicity is well documented. It is critical to consider the risk factors associated with nephrotoxicity while initiating TDF. The review provides evidence for calibrating the dosage of TDF based on body weight and BMI. Considering the high burden of PLHIV in India, prevention of nephrotoxicity through targeted and regular monitoring, early diagnosis and initiation of appropriate clinical management is crucial to reduce avoidable morbidity and mortality.